2018
DOI: 10.2217/fon-2017-0561
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CDK2 as a Novel Target in Treatment of Prostate Cancer

Abstract: These data indicated that CDK2 was a crucial factor in metastasis of Pca and might be a novel therapy target. [Formula: see text].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Many studies have suggested that CDK2 could be a crucial factor in the progression of cancer by regulating several pathways and might be a prospective biomarker and indicator of prognosis. Therefore, CDK2 and its cyclin binding partners are possible therapeutic targets for future cancer treatments (Yin et al, 2018;Zhang et al, 2018;Wood et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested that CDK2 could be a crucial factor in the progression of cancer by regulating several pathways and might be a prospective biomarker and indicator of prognosis. Therefore, CDK2 and its cyclin binding partners are possible therapeutic targets for future cancer treatments (Yin et al, 2018;Zhang et al, 2018;Wood et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CDKs are known to be upregulated during cancer and CDK inhibitors are used as anticancer drug trial (Goel et al 2018;J. H. Jeong et al 2009;Yin et al 2018;Malumbres and Barbacid 2009;Vijayaraghavan et al 2018). As a result, finding mangiferin targeting CDK4 as anticancer drug target has validated our approach (Figure 2).…”
Section: Discussionmentioning
confidence: 62%
“…CDKs are known to regulate cell-cycle phases and the overexpression of CDKs can induce cell proliferation (38,39). A previous study showed that inhibition of CDK2 suppressed PCa metastases by inactivating PI3K/Akt signaling (40). CDK5, CDK6, CDK7, and CDK9 can suppress CRPC through AR inactivation (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%